Oleic acid surfactant in polycaprolactone/hydroxyapatite‐composites for bone tissue engineering. Issue 6 (29th May 2015) - Cardoso, Guinea B. C.; Maniglio, Devid; Volpato, Fabio Z.; Tondon, Abhishek; Migliaresi, Claudio; Kaunas, Roland R.; Zavaglia, Cecilia A. C.
Abstract: Bone substitutes are required to repair osseous defects caused by a number of factors, such as traumas, degenerative diseases, and cancer. Autologous bone grafting is typically used to bridge bone defects, but suffers from chronic pain at the donor‐site and limited availability of graft material. Tissue engineering approaches are being investigated as viable alternatives, which ideal scaffold should be biocompatible, biodegradable, and promote cellular interactions and tissue development, need to present proper mechanical and physical properties. In this study, poly(ε‐caprolactone) (PCL), oleic acid (OA) and hydroxyapatite (HAp) were used to obtain films whose properties were investigated by contact angle, scanning electron microscopy, atomic force microscopy, tensile mechanical tests, and in vitro tests with U2OS human osteosarcoma cells by direct contact. Our results indicate that by using OA as surfactant/dispersant, it was possible to obtain a homogenous film with HAp. The PCL/OA/Hap sample had twice the roughness of the control (PCL) and a lower contact angle, indicating increased hydrophilicity of the film. Furthermore, mechanical testing showed that the addition of HAp decreased the load at yield point and tensile strength and increased tensile modulus, indicating a more brittle composition vs. PCL matrix. Preliminary cell culture experiments carried out with the films demonstrated that U2OS cells adhered and proliferated on all surfaces. The data demonstrate the improved dispersion of HAp using OA and the important consequences of this addition on the composite, unveiling the potentially of this composition for bone growth support. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 1076–1082, 2016.